1994
DOI: 10.1029/94wr01968
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diurnal variations in stream temperature on streamflow loss and groundwater recharge

Abstract: We demonstrate that for losing reaches with significant diurnal variations in stream temperature, the effect of stream temperature on streambed seepage is a major factor contributing to reduced afternoon streamflows. An explanation is based on the effect of stream temperature on the hydraulic conductivity of the streambed, which can be expected to double in the 0 ø to 25øC temperature range. Results are presented for field experiments in which stream discharge and temperature were continuously measured for sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
115
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 190 publications
(123 citation statements)
references
References 25 publications
7
115
1
Order By: Relevance
“…Such DOC concentrations are akin to those reported for a similar sized agricultural catchment in northern France [Morel et al, 2009] but relatively high when compared to values reported from many mixed-use catchments in both Europe and North America [Raymond and Oh, 2007;Monteith et al, 2007]. Base flow NO 3 -N concentrations of around 6.5 mg/L were similar to those reported previously for agricultural catchments [Lloyd et al, 2016b;Thomas et al, 2016] and were likely driven by current fertilizer application and legacy fertilizer At diurnal scales, streamflow exhibited minor fluctuations during base flow conditions, most likely driven by contrasts in evapotranspiration demand between day and night but also potentially due to temperaturedriven changes in water viscosity and associated changes in bed sediment hydraulic conductivity [Schwab et al, 2016;Constantz et al, 1994]. Observed daily cycles in NO 3 -N and DOC concentrations during base flow-dominated periods are likely to reflect a combination of minor dilution effects (in relation to diurnal changes in streamflow) and in-stream assimilatory uptake by microbial communities, which Rode et al…”
Section: Temporal Dynamics Of Streamflow No 3 -N and Docsupporting
confidence: 54%
“…Such DOC concentrations are akin to those reported for a similar sized agricultural catchment in northern France [Morel et al, 2009] but relatively high when compared to values reported from many mixed-use catchments in both Europe and North America [Raymond and Oh, 2007;Monteith et al, 2007]. Base flow NO 3 -N concentrations of around 6.5 mg/L were similar to those reported previously for agricultural catchments [Lloyd et al, 2016b;Thomas et al, 2016] and were likely driven by current fertilizer application and legacy fertilizer At diurnal scales, streamflow exhibited minor fluctuations during base flow conditions, most likely driven by contrasts in evapotranspiration demand between day and night but also potentially due to temperaturedriven changes in water viscosity and associated changes in bed sediment hydraulic conductivity [Schwab et al, 2016;Constantz et al, 1994]. Observed daily cycles in NO 3 -N and DOC concentrations during base flow-dominated periods are likely to reflect a combination of minor dilution effects (in relation to diurnal changes in streamflow) and in-stream assimilatory uptake by microbial communities, which Rode et al…”
Section: Temporal Dynamics Of Streamflow No 3 -N and Docsupporting
confidence: 54%
“…He found that when temperature of the infiltrating water is controlled by daily heating and cooling, the infiltration rate can show a marked diurnal variation, with maximum infiltration occurring during the day and minimum infiltration occurring at night. Constantz et al [1994] used diurnal variations in stream temperature to explain diurnal variations in streamflow measured in two streams, one in Colorado and one in New Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies of stream-aquifer interactions studied the effect of temperature on the kinematic viscosity of the water and, thus, the hydraulic conductivity. Constantz et al (1994) discussed diurnal temperature effects on seepage rates. That study demonstrated qualitatively that the effect of temperature was the main reason for the variability in daily streamflow losses.…”
Section: Introductionmentioning
confidence: 99%